1989
DOI: 10.1056/nejm198912283212603
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Comparing Combination Electron-Beam Radiation and Chemotherapy with Topical Therapy in the Initial Treatment of Mycosis Fungoides

Abstract: Mycosis fungoides is a T-cell lymphoma that arises in the skin and progresses at highly variable rates. Nonradomized studies have suggested that early aggressive therapy may improve the prognosis in this usually fatal disease. We studied 103 patients with mycosis fungoides, who, after complete staging, were randomly assigned to receive either combination therapy, consisting of 3000 cGy of electron-beam radiation to the skin combined with parenteral chemotherapy with cyclophosphamide, doxorubicin, etoposide, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
188
1
13

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(202 citation statements)
references
References 28 publications
0
188
1
13
Order By: Relevance
“…92,93 Gastrointestinal toxicity has been frequently noted, usually within 2 h of BCNU administration, and renal dysfunction has been reported in patients exposed to large cumulative doses. 95 96 The combination therapy achieved a significantly higher CR rate but at the expense of considerable toxicity. Importantly, after a median follow-up of 75 months, there was no difference between the treatment groups in terms of PFS or overall survival.…”
Section: Topical Bcnumentioning
confidence: 98%
See 1 more Smart Citation
“…92,93 Gastrointestinal toxicity has been frequently noted, usually within 2 h of BCNU administration, and renal dysfunction has been reported in patients exposed to large cumulative doses. 95 96 The combination therapy achieved a significantly higher CR rate but at the expense of considerable toxicity. Importantly, after a median follow-up of 75 months, there was no difference between the treatment groups in terms of PFS or overall survival.…”
Section: Topical Bcnumentioning
confidence: 98%
“…Importantly, after a median follow-up of 75 months, there was no difference between the treatment groups in terms of PFS or overall survival. 96 Hence, aggressive treatment with radiation and chemotherapy does not improve prognosis in patients with early-stage MF compared with those treated with standard SDT. 96 The EORTC Workshop meeting recommended that systemic chemotherapy should not be used at this disease stage.…”
Section: Topical Bcnumentioning
confidence: 99%
“…For many patients, this may involve either expectant management (i.e., ''watch and wait'') or skin-directed therapies. A randomized trial comparing early combined modality therapy with both radiation and multiagent chemotherapy (cyclophosphamide, doxorubicin, etoposide, and vincristine) with sequential topical therapies demonstrated that combined modality therapy, while associated with a superior complete response rate, did not translate into improvements in disease-free or overall survival, but was associated with significant toxicity [198]. Therefore, patients with limited-stage disease who require therapy are best approached with skin-directed therapies, usually under the direction of a dermatologist and/or radiation oncologist.…”
Section: Treatment Of Limited-stage Mfmentioning
confidence: 99%
“…As for limited-stage disease, multiagent chemotherapy, with only few exceptions, is generally not appropriate [198]. As summarized in Fig.…”
Section: Treatment Of Advanced-stage Mf/ss Overviewmentioning
confidence: 99%
“…A randomized study between TSEBI plus concurrent chemotherapy and local skin treatment with mustin found, at early stages. no difference in the rates of remission or relapse-free survival in either arm of the study (146). A pilot study of TSEBI combined with retinoid did not show better results than radiotherapy alone (147).…”
Section: Skin Lymphomamentioning
confidence: 86%